Impacts of ammonium based ionic liquids alkyl chain on thermodynamic hydrate inhibition for carbon dioxide rich binary gas - Khan, M.S. (Elsevier B.V., 2018)
In this work, the thermodynamic inhibition impact of four ammonium-based ionic liquids (AILs) on CO2 rich mixed gas hydrate system (70â30 mol CO2 + CH4) is experimentally studied, and the observed behaviour is modelled. The studied AILs are; tetramethylammonium hydroxide (TMAOH), tetraethylammonium hydroxide (TEAOH), tetrapropylammonium hydroxide (TPrAOH) and tetrabutylammonium hydroxide (TBAOH). Initially, the impact of 10 wt AILs in an aqueous solution on the CO2 enriched binary gas phase boundary is evaluated by measuring the dissociation temperature in the pressure range of 1.90â5.10 MPa. The thermodynamic inhibition influence of AILs is quantitatively analyzed by calculating the hydrate suppression temperatures for all studied systems. Further, the ClausiusâClapeyron equation is used to determine the molar hydrate enthalpy of dissociation (âHdiss) for the studied systems. The results revealed that the inhibition influence of AILs is observed to be decreasing with the increasing alkyl chain length of AILs. Excluding TBAOH, all the other studied AILs act as thermodynamic inhibitors due to the relatively shorter alkyl chain. The âHdiss results of the binary mixed gas system in the presence and absence of AILs revealed that the presence of TMAOH, TEAOH and TPrAOH has negligible effect in hydrate cages formation. However, TBAOH exhibited a significant change in âHdiss which indicates the semi-clathratic nature of it. Among the considered AILs, TMAOH shown better thermodynamic impact attributed to its shortest alkyl chain length. Therefore it is further investigated for various concentrations (1, 5 and10 wt). Moreover, the measured, mixed gas hydrate phase boundaries of various aqueous AILs solutions are also predicted via electrolyte model proposed by Dickens and Quinby-Hunt and are found to be in good agreement with the experimental data apart from TBAOH. Therefore, this study is relevant for the understanding of structural variations (alkyl chain elongation) of AILs on the hydrate phase stability of the high CO2 content mixed gas system. Â© 2018 Elsevier B.V.